Broadway : the American musical - Maslon, Laurence; Kantor, Michael, 1961- (New York : Bulfinch Press, 2004)
Presents a history of the Broadway musical theater, including summaries of the shows, photographs of the stars, posters, sheet music, production stills, and essays by theater luminaries.
A real live nephew of my Uncle Sam's (1893-1919) -- Syncopated city (1920-1930) -- I got plenty o' nuttin' (1931-1942) -- Oh, what a beautiful mornin' (1943-1959) -- Tradition (1960-1979) -- The Lullaby of Broadway (1980-2004).
Includes bibliographical references (p. 449-453) and index.
Keywords: Musicals -- New York (State) -- New York -- History and criticism; Musicals -- New York City (N.Y.) -- History and criticism